Tests of fed and unfed Amblyomma cajennense ticks (Acari: Ixodidae): first morphological data - Anholeto, Luis Adriano [UNESP]; Nunes, Pablo Henrique [UNESP]; Remedio, Rafael Neodini [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2015)
The tick species Amblyomma cajennense is of great medical importance, as it is the vector of the Rickettsia rickettsii, agent of Rocky Mountain spotted fever. The objective of this study was to perform a morphological and histological analysis of the male reproductive system of fed and unfed A.cajennense. The male reproductive system is formed by a pair of tubular testes dorsolaterally arranged in opisthosoma. They were divided into three regions: proximal region (next to vas deferens), median region and distal region (nearest to the blind ending of testis). Proximal regions are connected to the seminal vesicles by the deferent ducts and to accessory glands, similar to what was observed for other Ixodidae. Feeding plays a fundamental role in the development of the reproductive system, as in unfed individuals, the testes, the seminal vesicles and the accessory glands were smaller comparing with the fed individuals. In addition, the prospermia, precursors of the spermatozoa, were only observed in fed individuals. The germ cells were organized in spermatocysts, enveloped by a connective tissue. The cells in more advanced stages of spermatogenesis were localized in the distal region, in accord with studies in other ticks, but opposite to what was observed for other arthropods.
Keywords: Histology; Testis; Ticks; Ixodidae; Reproductive system